Serum Paraoxonase Activity and Phenotype Distribution in Covid-19 Patients - Çelik H. İ.; Selek Ş.; Sönmez E.; Metin H.; Taslidere B.; Sarıkaya U.; Yurtsever İ.; Okay G.; Doymaz M. Z.; Gülen B. (My University, 2024)
Objective: For the phenotype classification, it is important to determine the relationship between enzyme activity and the severity of the COVID-19 disease. Reaching significant differences between healthy and infected individuals in terms of genotype and allele distributions may be a guide in the fight against the COVID-19 pandemic. This study, it was aimed to investigate the relationship between serum arylesterase PON1 enzyme activity and disease severity in COVID-19 patients. Methods: Patients over the age of 18 who applied to the Emergency Service between 01-30 April 2020 and were examined with a preliminary diagnosis of COVID-19 were included in the study. In the study, serum PON1 activity was measured in the venous blood of 56 patients diagnosed with Covid-19 disease by either CT or RT-PCR and who have not received any systemic treatment yet. Results: The Arylesterase (AREase) and Paraoxonase (POase) activity levels of the study and control groups were 131.49 ± 52.75 kU/L 142.29 ± 38.82 kU/L, 276.48 ± 220.4 U/L 505.30 ± 301.4 U/L, respectively. It was found that 64.3 % of those infected with Covid-19 had the low-activity PON1 phenotype (p= 0.007) Conclusion: Genetic variability in PON1 may be associated with exposure to or risk of developing the disease. As a result, vaccination of individuals with low activity phenotype can be given priority at the vaccination stage in order to reduce the mortality rate in the fight against the pandemic. Awareness and protection measures of societies with low activity phenotypes can be increased.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Clinical Medicine (Med); Clinical Medicine